Consumer Protection in Universal Coverage in Thailand : What is Missing? - ศิริสินสุข ยุพดี (Journal of Health Science of Thailand, 2021)
The study was aimed to summarize the existing situations and make the policy recommendation to improve the consumer protection system related to health insurance system in Thailand. The scope of the study has covered the assessment of five issues of people’s rights as follows: access to needed care through health insurance, access to quality care, access to complete benefit package, participation in health insurance management and access to necessary information. Focus group discussion and documentation review were used for data collections. Preliminary result was sent to community representatives in Provincial Health Security Sub-committee to make comments before finalizing the report. The results showed that there still were several problems regarding the people’s basic rights in utilizing health services under health insurance such as the problems of uninsured groups due to no identification card issued by the Ministry of Internal Affairs, the problems of specific groups of people who could not access to health benefit package including the disability, patients living with HIV and AIDS and the informal sector workers especially for high cost care and medications, lack of or inadequate information for general people, and low level of people participation in health insurance system. The policy recommendations to strengthen the consumer protection system covered in the report are: 1) actively search for uninsured groups by cooperating with all stakeholders, and set up the fund to support hospitals that are responsible for these uninsured: 2) support people to participate in all levels including policy formulation, health insurance management by civic organization and local government, monitoring service quality and the completeness of benefit package provided, and 3) widely distribute essential information including information for selecting the hospital, the information for deciding whether or not to receive some controversial health services or second opinion and the information to increase basic knowledge about health insurance and health service utilization.